Efficiency with Uncertain Supply - Diamond, Peter (Review of Economic Studies, 1980)
As Oliver Hart (1975) has forcefully shown, economies with incomplete markets can have surprising welfare properties. These examples, or counter-examples, bring out the need for further analysis of public policies in the presence of uncertainty and incomplete markets. Various policies are examined here in simple models with two goods, two types of agents, and two states of nature. The basic model has an ex ante decision by suppliers, made with rational expectations, followed by a competitive exchange economy after the state of nature is known. The paper analyses the changes in expected utilities of demanders and suppliers from small changes in the ex ante decision away from the competitive equilibrium. Such changes generally have the potential of increasing the sum of expected utilities and can result in a Pareto improvement. The paper focuses on distinguishing between situations where the gain comes from stabilizing output across states of nature and those where the gain comes from destabilizing. Then two policies are examined which work on the ex post market-use of taxes and subsidies to stabilize suppliers' incomes and use of government demand policy to maximize social welfare.